Pengaruh Hidroterapi dan William Flexion Exercise terhadap Penurunan Nyeri Low Back Pain - Wibisono LS; Putri AR; Najizah F; Syurrahmi Syurrahmi (Pusat Riset dan Inovasi Nasional, 2025)
Low back pain (LBP) is one of the most common musculoskeletal disorders and significantly impacts functional activities and patients’ quality of life. Non-pharmacological approaches such as hydrotherapy and William flexion exercise are widely used to reduce pain. Objective: This study aimed to determine the effect of combining hydrotherapy and William flexion exercise on reducing pain in patients with myogenic low back pain. Methods: This research applied a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 20 respondents aged 40–60 years who met the inclusion criteria. The intervention was conducted over 12 sessions within one month at Biara OSF Magdalena Daemen BSB. Pain levels were measured using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using the Paired Sample t-Test. Results: The findings revealed a significant reduction in pain levels. The mean pretest score of 43.36 increased to 79.45 in the posttest with a difference of 36.09 points. Statistical testing showed p = 0.001 (< 0.05), indicating that the combination of hydrotherapy and William flexion exercise had a significant effect on reducing low back pain. Hydrotherapy contributed to muscle relaxation and improved circulation, while William flexion exercise strengthened lumbar flexor muscles. Conclusion: The combination of hydrotherapy and William flexion exercise is effective in reducing myogenic low back pain. This approach can be considered a safe, applicable, and beneficial non-pharmacological rehabilitation strategy to improve patients’ quality of life.